Development of 3D printed resin reinforced with modified ZrO2 nanoparticles for long-term provisional dental restorations. Issue 6 (June 2021) - Aati, Sultan; Akram, Zohaib; Ngo, Hien; Fawzy, Amr S.
Graphical abstract: Highlights: ZrO2 with variable concentrations showed a homogenized dispersion and printability. ZrO2 improved resin sorption and solubility after 3 months of storage aging. ZrO2 enhanced mechanical properties. Abstract: Objective: To characterize and investigate efficacy of loading functionalized ZrO2 nanoparticles in 3-dimensional (3D) printed acrylate ester-based resin subjected to accelerated aging in artificial saliva. As well as to evaluate the effect of ZrO2 nanoparticle volume fraction addition on mechanical and physical properties of printed composite. Methods: Functionalized ZrO2 nanoparticles were characterized using TEM and Raman spectroscopy. 3D printed dental resin was reinforced, with ZrO2 nanoparticles, in the concentration range (0–5 wt.%). The resulted nanocomposites, in term of structure and physical/mechanical properties were evaluated using different mechanical testing, microscopic and spectroscopic techniques. Results: ZrO2 based nanocomposite was successful and formed composites were more ductile. Degree of conversion was significant at the highest level with blank resin and 1 wt.%. Sorption revealed reduction associated with volume fraction significant to neat resin, however solubility indicated neat and 4 wt.% had the lowest significant dissolution. Vickers represented critical positive correlation with filler content, while nanohardness and elasticity behaved symmetrically and had the maximum strength at 3 wt.% addition. In addition, 3 wt.% showed the highest fracture toughness and modulus. Improvement of flexural strength was significantly linked to filler concentration. Overall properties dramatically were enhanced after 3 months aging in artificial saliva, especially degree of conversion, microhardness, nanoindentation/elasticity, and flexural modulus. However, significant reduction was observed with flexural modulus and fracture toughness. Significance: The outcomes suggest that the newly developed 3D printed nanocomposites modified with ZrO2 nanoparticle have the superior potential and efficacy as long-term provisional dental restoration materials.